2015
DOI: 10.1093/ecco-jcc/jjv005
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of a New Fecal Marker, Matrix Metalloprotease-9, in Different Types of Inflammatory Bowel Diseases

Abstract: This is the first study assessing the diagnostic accuracy of MMP-9 in different types of IBD. Our results showed that fecal MMP-9 has high sensitivity in the detection of endoscopically active UC and pouchitis. These non-invasive methods help assess intestinal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 24 publications
7
33
0
1
Order By: Relevance
“…The activity of some MMPs (MMP-1, 2, 3 and 9) is also augmented in colon of IBD patients and is correlated with MPO level and tissue damage [106]. Strong associations are shown between faecal MMP-9 and clinical, endoscopic, and histologic activities of UC, but no correlation are found between this biomarker and activity indices of CD [107]. …”
Section: Role Of Neutrophil-derived Moleculesmentioning
confidence: 99%
“…The activity of some MMPs (MMP-1, 2, 3 and 9) is also augmented in colon of IBD patients and is correlated with MPO level and tissue damage [106]. Strong associations are shown between faecal MMP-9 and clinical, endoscopic, and histologic activities of UC, but no correlation are found between this biomarker and activity indices of CD [107]. …”
Section: Role Of Neutrophil-derived Moleculesmentioning
confidence: 99%
“…Despite MMP-9 being elevated in both CD and UC, the performance of MMP-9 as a disease marker appears to be better in UC and pouchitis [65]. Kolho et al [66] compared the performance of MMP-9 to that of calprotectin in distinguishing IBD from non-IBD subjects.…”
Section: Matrix Metalloproteinasementioning
confidence: 99%
“…Potential biomarkers are constantly being discovered [48]- [50]. Recent studies on neopterin demonstrated its ability to identify patients with IBD with active mucosal lesions and could potentially be used to assess the severity their mucosal damage [51].…”
Section: Other Markersmentioning
confidence: 99%